Control and communication of renewable energy based smart grid: an overview - Surender Reddy, S (International Journal of Engineering and Technology, 2018)
Smart Grid (SG) involves complex controls and communications. These controls include both the local as well as global controls. SG in-volves a two-way communication system at each stage and that is one of the advantages over the conventional utility grid. However, due to this two-way communications, the issues such as complexity, data gathering and management, etc, are introduced into the SG system. Therefore, this new grid requires a more complex and control operation. The objective of this paper is to evaluate various control systems, communication technologies, and real time measurement tools that are involved in the SG. This paper also performs the cost benefit analysis (CBA) of the control and communication schemes involved in the SG. The paper evaluates the latest tools for control and communications that are available, and it also evaluates the issues and challenges relative to it.Â Â